Teleworking for Medical Reasons: Evidence From a Spanish Multinational Company - Reinoso-Barbero, Luis; Gieco, Antonella; López-Ríos, Adriana; Rodríguez-Díaz, José Luis; Gómez-Paredes, Laura; Muñoz-Gutiérrez, Juan; Pérez-Herreras, Cristina; Gómez-Gallego, Félix (Journal of Occupational and Environmental Medicine, 2026)
Objectives: The aim of the study is to describe the most common medical grounds for requesting or extending teleworking and to examine which requests are typically approved. This study also investigates whether there is a correlation with gender, age, or job location. Methods: A prevalence study of 33,190 Spanish employees found that, last year, 106 teleworking requests were addressed exclusively for medical reasons. Results: The most frequent cause was musculoskeletal issues (30%). Of all the requests, 58% were denied; 33% were temporarily approved, primarily for musculoskeletal reasons (P < 0.05); and 8% were indefinitely approved. Requests were predominantly made by women (P < 0.05). Indefinite approvals were more prevalent among male employees (P < 0.05). Conclusions: Musculoskeletal reasons were the primary cause for teleworking applications and for the temporary granting of teleworking. Teleworking appears to be associated with gender and job location
Keywords: medical reasons, teleworking, telecommuting, workplace, occupational medicine, occupational health; medical reasons; teleworking; telecommuting; workplace; occupational medicine; occupational health